Recent progress in the description of positron scattering from atoms using the convergent close-coupling theory - Kadyrov, Alisher; Bray, I. (Institute of Physics Publishing Ltd., 2016)
© 2016 IOP Publishing Ltd. Much progress in the theory of positron scattering on atoms has been made in the ten years since the review of Surko et al (2005 J. Phys. B: At. Mol. Opt. Phys. 38 R57). We review this progress for few-electron targets with a particular emphasis on the two-centre convergent close-coupling and other theories which explicitly treat positronium (Ps) formation. While substantial progress has been made for Ps formation in positron scattering on few-electron targets, considerable theoretical development is still required for multielectron atomic and molecular targets.